Active Learning : Social Studies Teaching and Learning in the 21st Century - Wanthum, Pornchai; Namseethan, Somkhuan; Phrakhusunthonwinairot; Ketchan, Thongkham; Kusalacitto, Phrakhruthammathon Weerayut (Journal of Buddhist Education and Research (JBER), 2024)
Active Learning in social studies teaching for the 21st century represents a synthesis of concepts focused on learner-centered approaches. This method of learning aligns with the demands of 21st-century education by shifting the role of teachers to facilitators and empowering students to take a more active role in their own learning. It emphasizes hands-on experiences that allow learners to interact with peers and teachers through collaborative activities both inside and outside the classroom. This approach fosters direct experiential learning, enhancing student engagement and participation. To implement social studies teaching in the 21st century effectively, it is essential to adopt principles, processes, and methodologies that cultivate practical skills through real-world experiences. These skills include knowledge acquisition, moral and ethical development, and social coexistence. Active Learning aims to develop these competencies, enabling learners to apply their knowledge and skills in meaningful ways while fostering values necessary for living harmoniously in society.